Identification and biochemical characterization of a second zebrafish autotaxin gene. (10th January 2019) - Kise, Ryoji; Okasato, Ryohei; Kano, Kuniyuki; Inoue, Asuka; Kawahara, Atsuo; Aoki, Junken
Abstract: Autotaxin (ATX) is a secreted enzyme that produces a bioactive lysophospholipid, lysophosphatidic acid (LPA). ATX plays a role in vascular and neural development in embryos but its mechanisms remain unclear. At the beginning of this study, only one zebrafish atx gene ( atxa ) was known and had been investigated. In this study, we generated ATX knockout (KO) fish by TALEN targeting atxa . Unexpectedly, atxa KO fish showed neither vascular defects nor reduction of ATX activity, implying the existence of one or more other ATXs in the genome. By a BLAST search using ATXa protein fragments as a query, we found a genomic sequence that closely resembled atxa exons 13, 14 and 15. Consequently, we cloned a cDNA encoding a second zebrafish autotaxin (ATXb), and found that it was transcribed in various tissues. The atxb gene encoded a protein of 832 amino acids (compared to 850 amino acids in ATXa) with 60% amino acid identity to ATXa and clustered with ATXs from other species. A recombinant ATXb protein showed lysophospholipase D (lysoPLD) activities with substrate specificities similar to those of ATXa and mammalian ATXs. These results indicate that ATXb is a second zebrafish ATX, which possibly shares redundant roles with ATXa in embryonic development.